2016
DOI: 10.5539/ijef.v8n5p260
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Reactions of China’s Stock Market to Short-Term Interest Rates

Abstract: This paper investigates how China's stock market reacts to short-term interest rates, as represented by the Shanghai Interbank Offered Rate (Shibor). We adopt the Markov Regime Switching model to divide China's stock market into Medium, Bull and Bear market; and then examine how Shibor influences market returns and risk in different market regimes. We find that short-term interest rates have a significant negative effect on stock returns in Medium and Bull market, but could not affect stock returns in Bear mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The study uses a log of daily stock returns from the Shanghai Stock Exchange Composite Index and three-month interest rates over the period from 2013 to 2015. The study shows that interest rates help in forecasting stock returns in China, which also confirm the findings of Fang et al, (2016) that interest rates have a significant effect on stock returns.…”
Section: Interest Ratessupporting
confidence: 85%
“…The study uses a log of daily stock returns from the Shanghai Stock Exchange Composite Index and three-month interest rates over the period from 2013 to 2015. The study shows that interest rates help in forecasting stock returns in China, which also confirm the findings of Fang et al, (2016) that interest rates have a significant effect on stock returns.…”
Section: Interest Ratessupporting
confidence: 85%
“…Some studies found a negative relationship between interest rates and equity markets. The studies include Haider (2018), Laichena and Obwogi (2015), Okech and Mugambi (2016), Okechukwu et al (2019), Fang et al (2016), Shula (2017), Bature et al (2019), Pilinkus and Boguslauskas (2015), Khalid (2017), Ibrahim and Musah (2014), Teitey (2019), Florackis et al (2014), Marfatia (2014), Hashim et al (2018); Najaf and Najaf (2017); Osei (2016); Khan and Khan (2018), Shrestha and Subedi (2014), Msindo (2015), Dima (2015), Mutheu (2016), Mahzabeen (2016), Ali (2014), Gu et al (2021), Setiawan (2020), andMapolisa (2019).…”
Section: Empirical Studiesmentioning
confidence: 99%
“…These findings are similar to those in Fang et al . (2016), who investigate how China’s stock market reacts to changes in the Shanghai Interbank Offered Rate (Shibor). They find that market reaction depends on the state of the economy and conclude that China’s market appears quite distinct from the US market or the markets of other developed countries.…”
Section: Main Analysismentioning
confidence: 99%